Predictive Value of Random Blood Sugar, Hemoglobin A1c, and Zinc Deficiency for Insulin Resistance in Patients with Type 2 Diabetes Mellitus - Hawre Tahir, Naz; Hadi, Pary; Salah Mawlood, Muhanad; Merza, Mohammed (Journal of Neonatal Surgery, 2025)
This study was conducted to explore the relationship between glycemic indicators, zinc deficiency, and insulin resistance in individuals with type 2 diabetes. The study took place at the Leila Qasm Diagnostic Center in Erbil, Iraq, between November, 2024 and March, 2025. It included 200 patients diagnosed with type 2 diabetes and 200 healthy individuals as controls. Blood samples were collected and analyzed for serum markers using the Cobas Integra system. Compared to the healthy controls, patients with type 2 diabetes showed significantly lower serum zinc levels and higher levels of random blood glucose, HbA1c, and HOMA-IR. Correlation analysis revealed a negative association between serum zinc and insulin resistance, while both random blood glucose and HbA1c were positively correlated with insulin resistance. Multiple linear regression analysis identified zinc deficiency and elevated HbA1c as significant predictors of increased HOMA-IR in diabetic patients. In conclusion, type 2 diabetes, reduced serum zinc along with elevated random blood glucose and HbA1c levels are strong predictors of increased insulin resistance.